1998
DOI: 10.1007/s002709900231
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic Fibrinolysis with rt-PA: In Vitro Results

Abstract: Activity of rt-PA-induced fibrinolysis rises distinctly with higher temperatures. Since even healthy subjects show a physiologic decline in body temperature in the extremities, in patients with occlusive arterial disease decreased activity of fibrinolysis with rt-PA can be expected. Controlled hyperthermia may improve fibrinolysis with rt-PA and should be investigated in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…After addition of tPA, concentration of D-dimer was approximately tripled and time to complete clot lysis was approximately halved from 30°C to 40°C. 16 Our present results also show an increase in fibrinolytic activity of tPA at higher temperatures as indicated by significant decrease in clot size at higher temperatures. These results thus suggest that the increased fibrinolytic activity of tPA during hyperthermia is offset by its deleterious actions and a net Effects of hyperthermia on perfusion deficit after focal cerebral ischemia.…”
Section: Discussionsupporting
confidence: 83%
“…After addition of tPA, concentration of D-dimer was approximately tripled and time to complete clot lysis was approximately halved from 30°C to 40°C. 16 Our present results also show an increase in fibrinolytic activity of tPA at higher temperatures as indicated by significant decrease in clot size at higher temperatures. These results thus suggest that the increased fibrinolytic activity of tPA during hyperthermia is offset by its deleterious actions and a net Effects of hyperthermia on perfusion deficit after focal cerebral ischemia.…”
Section: Discussionsupporting
confidence: 83%
“…In vitro studies showed an increase in fibrinolytic activity at high temperatures [35], and in a recent study in 111 patients treated with tPA, high temperatures at admission were associated with a better outcome [36]. These results have not been validated by other studies [12], [36], [37], but have shown results similar to ours [38].…”
Section: Discussionmentioning
confidence: 50%
“…There is evidence from previous studies that hyperthermia facilitates the process of tPA-induced thrombolysis. 27,28 In our study where all the patients underwent tPA thrombolysis, the absence of any relationship between hyperthermia before thrombolysis and poor outcome could be explained by this process.…”
Section: Discussionmentioning
confidence: 75%